Karakter Habitus dan Viabilitas Biji Tanaman Biduri (Calotropis gigantea) Aksesi Lombok Tengah Bagian Selatan - Yuliani Ahmad; M. Taufik Fauzi; Bambang Budi Santoso (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
This study aims to describe the morphological character and seed growth potential of biduri (Calotropis gigantea) accession growing in the tourist area of South Central Lombok (Kuta Mandalika, Tanjung Aan, and Seger), and was carried out during February-August 2020. The method used was descriptive observative with survey techniques and sampling by purposive sampling based on the population of biduri. The seed growth experiment used a completely randomized design in a greenhouse consisting of two factors, namely the type of substrate and accession, which was repeated three times, so that there were 18 experimental units. The results shows that the Kuta Mandalika Biduri accession was showed superiority in the number of fruit characters per panicle. Tanjung Aan accessions excel in branching characters (primary and secondary branches), number of panicles per tree, number of flowers per panicle, number of fruits per tree and fruit size. Meanwhile, Seger accessions were superior in terms of plant height, seed size and weight of 100 seeds. There were no character differences in seed viability of the three accessions. The closest genetic-relationship occurs in the Kuta Mandalika accession of plot 2 sample 2 with the Kuta Mandalika accession of plot 3 sample 1 marked with a coefficient value of 1.00. Meanwhile, the furthest relationship was found in the Kuta Mandalika accession of plot 1 sample 1 with Tanjung Aan accession of plot 2 sample 2 marked with a coefficient value of 33.932.